Compiuta Donzella or a Feminine Voice in "Volgare" Poetry - Hapon, Katarzyna (ItaliAMO: Promotion of Italian Studies in the Academic and Non-Academic Environment, 2023)
The paper introduces the silhouette of medieval Italian poetess Compiuta Donzella. The authoress introduces basic information about her work and interprets chosen passages of her texts.